Coupling Characteristics of Fused Optical Fiber Coupler Formed with Single-Mode Fiber and Photonic Crystal Fiber Having Air Hole Collapsed Taper. (24th November 2016) - Yokota, Hirohisa; Yashima, Hirotomo; Imai, Yoh; Sasaki, Yutaka
Abstract : Fused coupler forming with a single-mode fiber (SMF) and a photonic crystal fiber (PCF) is one of the solutions for optical coupling from a light source to a PCF. In this paper, we presented coupling characteristics of a fused fiber coupler formed with an ordinary SMF and a PCF having air hole collapsed taper. A prototype of SMF-PCF coupler with air hole collapsed taper was fabricated using CO2 laser irradiation. The coupling efficiency from SMF to PCF was −6.2 dB at 1554 nm wavelength in the fabricated coupler. The structure of the SMF-PCF coupler to obtain high coupling efficiency was theoretically clarified by beam propagation analysis using an equivalent model of the coupler with simplification. It was clarified that appropriately choosing the prestretched or etched SMF diameter and the length of air hole collapsed region was effective to obtain high coupling efficiency that was a result of high extinction ratio at cross port and low excess loss. We also demonstrated that the diameter of prestretched SMF to obtain high coupling efficiency was insensitive to the air hole diameter ratio to pitch of the PCF in the air hole collapsed SMF-PCF coupler.